ECE671: Introduction to Computer Graphics / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2014)
This course provides an introduction of the major topics in computer graphics. Topics include line drawing, planes, vectors, 2-D and 3-D representation, 2-D and 3-D transformations, 3-D viewing and projection, geometric modeling and rendering.